Operational Performance Analysis of the Cryogenic Electrical Machine for Submerged Liquefied Natural Gas Pumps - Guo, Chao; Feng, Yaojin; Huang, Shoudao; Wang, Jiabao (Frontiers in Energy Research, 2022)
The electrical machine is one of the key components for submerged liquefied natural gas (LNG) pumps. This paper deals with a cryogenic permanent magnet synchronous motor (CPMSM) for submerged LNG pump. An 18.5kW CPMSM prototype was developed according to the needs of users. Basic design of the CPMSM is proposed by using a cryogenic temperature (CT) design method. To analyze the operational performance accurately, simulation modeling and analysis are carried out and a liquid nitrogen (-196℃) experimental platform is built. The test results verify the rationality of the design and the accuracy of the simulation. Based on the simulation and experimental data, the working characteristics and mechanical properties of the prototype in the liquid nitrogen are analyzed. In addition, the performance of the prototype operating in liquid nitrogen (-196℃) and LNG (-161℃) are compared and analyzed, and the results show that the operating characteristics of the prototype in the two fluid environments are similar.